2014
DOI: 10.1017/s0960129514000267
|View full text |Cite
|
Sign up to set email alerts
|

Characterizingco-NLby a group action

Abstract: In a recent paper, Girard proposes to use his recent construction of a geometry of interaction in the hyperfinite factor in an innovative way to characterize complexity classes. We begin by giving a detailed explanation of both the choices and the motivations of Girard's definitions. We then provide a complete proof that the complexity class co-NL can be characterized using this new approach. We introduce as a technical tool the non-deterministic pointer machine, a concrete model to computes algorithms.Comment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 21 publications
(19 reference statements)
1
55
0
Order By: Relevance
“…Using the crossed product construction between a von Neumann algebra and a group acting on it, he proposed to characterize complexity classes as sets of operators obtained through the internalization of outer automorphisms of the type II 1 hyperfinite factor. The authors showed in a recent paper [2] that this approach succeeds in defining a characterization of the set of co-NL languages as a set of operators in the type II 1 hyperfinite factor. The proof of this result was obtained through the introduction of non-deterministic pointer machines, which are abstract machines designed to mimic the computational behavior of operators.…”
Section: A New Approach To Complexitymentioning
confidence: 99%
See 4 more Smart Citations
“…Using the crossed product construction between a von Neumann algebra and a group acting on it, he proposed to characterize complexity classes as sets of operators obtained through the internalization of outer automorphisms of the type II 1 hyperfinite factor. The authors showed in a recent paper [2] that this approach succeeds in defining a characterization of the set of co-NL languages as a set of operators in the type II 1 hyperfinite factor. The proof of this result was obtained through the introduction of non-deterministic pointer machines, which are abstract machines designed to mimic the computational behavior of operators.…”
Section: A New Approach To Complexitymentioning
confidence: 99%
“…1 The construction L 2 (G, H) is a generalization of the well-known construction of the Hilbert space of square-summable functions: in case G is considered with the discrete topology, the elements are functions f : G → H such that g∈G f (g) 2 < ∞. 2 Recall that in the algebra L (H) of bounded linear operators on the Hilbert space H (we denote by 〈·, ·〉 its inner product), there exists an anti-linear involution (·) * such that for any ξ, η ∈ H and A ∈ L (H), 〈Aξ, η〉 = 〈ξ, A * η〉. This adjoint operator coincides with the conjugate-transpose in the algebras of square matrices.…”
Section: The Basic Picturementioning
confidence: 99%
See 3 more Smart Citations